Pain Assessment in INTensive care (PAINT): an observational study of physician‐documented pain assessment in 45 intensive care units in the United Kingdom. (19th February 2017) - Kemp, H. I.; Bantel, C.; Gordon, F.; Brett, S. J.; ,; ,; Laycock, H. C.
Summary: Pain is a common and distressing symptom experienced by intensive care patients. Assessing pain in this environment is challenging, and published guidelines have been inconsistently implemented. The Pain Assessment in INTensive care (PAINT) study aimed to evaluate the frequency and type of physician pain assessments with respect to published guidelines. This observational service evaluation considered all pain and analgesia‐related entries in patients' records over a 24‐h period, in 45 adult intensive care units (ICUs) in London and the South‐East of England. Data were collected from 750 patients, reflecting the practice of 362 physicians. Nearly two‐thirds of patients (n = 475, 64.5%, 95%CI 60.9–67.8%) received no physician‐documented pain assessment during the 24‐h study period. Just under one‐third (n = 215, 28.6%, 95%CI 25.5–32.0%) received no nursing‐documented pain assessment, and over one‐fifth (n = 159, 21.2%, 95%CI 19.2–23.4)% received neither a doctor nor a nursing pain assessment. Two of the 45 ICUs used validated behavioural pain assessment tools. The likelihood of receiving a physician pain assessment was affected by the following factors: the number of nursing assessments performed; whether the patient was admitted as a surgical patient; the presence of tracheal tube or tracheostomy; and the length of stay in ICU. Physician‐documented pain assessments in the majority of participating ICUs were infrequent and did not utilise recommended behavioural pain assessment tools. Further research to identify factors influencing physician pain assessment behaviour in ICU, such as human factors or cultural attitudes, is urgently needed.